A Pragmatic Analysis On Directive Utterances In Despicable Me Movie And It's Subtitle - Prayitno, Joko Dwi; , Siti Zulaekah, A, M.Si; , Dr. Dwi Haryanti, M.Hum (2014)
This study aims at describing the varieties of pragmalinguistics form, the equivalence of illocutionary act and the equivalence of politeness pattern on directive utterances in Despicable Me movie and it's subtitle. This research uses descriptive qualitative research. The data are sentence containing directive acts in Despicable Me movie and it's subtitle. Documentation and observation are method to collect the data. Based on the result of the data analysis, the writer finds that 1) the varieties of pragmalinguistics form are 32 (26.7%) data using internal modification of pragmalinguistics form. 13 (12.5%) data using syntactic downgraders, 17 (14.2%) data using Lexical/ Phrasal downgraders and 1 (0.8%) datum combining of syntactic and lexical/ phrasal downgraders and upgraders. 2) in the equivalence of illocutionary act, the writer finds 119 (99.17%) data equivalence. They are 61 (50.83%) data of requesting, 46 (38.33%) data of commanding and 6 (5%) data of suggesting and warning. The writer finds only 1 (0.8%) datum non equivalence in the form of commanding. 3) in the equivalence of politeness pattern, the writer finds 115 (95.83%) data equivalence. They are 59 (49.17%) data that using bald on record strategy. 39 (32.5%) data using positive politeness strategy. 14 (11.7%) data using negative politeness strategy and 3 (2.5%) data using off record of politeness strategy. The writer finds 5 (4.17%) data non equivalence. 2 (1.67%) data of positive politeness strategy and 3 (2.5%) data of negative politeness.